Helping Trainees Develop Scholarship in Academic Medicine From Community Service - Sunny Nakae; Maria Soto-Greene; Renee Williams; Daniel Guzman; John P. Sánchez (Association of American Medical Colleges, 2017)
Introduction Service in the community and academic medicine are often seen by trainees as unrelated. This may be one reason for the lack of faculty diversity and the declining interest in academic medicine among new trainees. Methods We developed an educational workshop through the application of the Kern model to help medical students and residents understand the relationship between community service work and scholarship as it pertains to a career in academic medicine. Specifically, the workshop helped trainees (1) understand the terms service and scholarship, (2) understand the benefits of achieving community service scholarship, and (3) identify steps to achieve community service scholarship through mock cases and personal stories. Results The workshop was implemented at five conferences with a total of 139 trainees. Results of a paired-samples t test of learners' responses pre- and postworkshop showed statistically significant growth in their confidence to publish service-related work, as well as more positive agreement with the notion that community service work aligns with an academic medicine career. Discussion This effective module can help trainees understand how community service and academic medicine are aligned, and raise their confidence in building a foundation for an academic medicine career through conducting community service scholarship.